Genetically and chemically intraspecific variations of Ficus hirta provide novel insights into its protection and utilization - Jianling Chen; Qianqian Liu; Huihong Wang; Zhi Chao; Enwei Tian (BMC Plant Biology)
Abstract Background Radix Fici Hirtae, the dry root of Ficus hirta, is a famous ethnomedicine and food that has been widely used by Yao and Zhuang nationalities in southern China for its potent antitumor, antifungal, and hepatoprotective effects. Recently, owing to over-exploitation and habitat destruction, F. hirta has been pushed to the brink of depletion. In addition, cultivation and breeding have resulted in severe intermixing and degeneration over the past 20 years. However, little is known about the genetic background and medicinal quality of F. hirta across populations, which restricts its protection and utilization. In this study, we conducted an evaluation of the chloroplast DNA (cpDNA) genetic diversity and population structure of F. hirta in southern China, and further evaluated its medicinal quality based on HPLC fingerprinting and the content determination of the active components. Results F. hirta presented high overall genetic diversity (Hd = 0.792) for cpDNA but low genetic diversity (Hd = 0.000 ~ 0.467) within populations. All seventeen populations were genetically assigned into two groups, most of which were not geographically clustered together. Mantel test revealed no significant isolation by distance pattern for F. hirta (P = 0.233), which might be related to its habitat fragmentation. High population differentiation (F ST = 0.912) was detected in F. hirta, and AMOVA revealed that 91.17% of cpDNA variation occurred between populations. HPLC fingerprint analysis indicated that most F. hirta samples derived from 14 geographic origins had highly similar components (similarity = 0.828 ~ 0.975). Fourteen origins of F. hirta were clustered into three groups by HCA, PCA and OPLS-DA. Psoralen and bergapten were the differentiated quality markers among the groups. The medicinal quality of the populations NN, SD and HZ within southwestern group was much greater than that of the ND and GZ populations within southeastern group, which is consistent with the comprehensive quality scores for each origin (Y = 1.78 ~-0.82). The medicinal quality formation of F. hirta was highly correlated with geographical environment but not with cpDNA genetic variation. Conclusions F. hirta presented high overall genetic diversity and population differentiation, but without significant isolation by distance, which might relate to its habitat fragmentation. Different geographic origins’ Radix Fici Hirtae were chemically clustered into three groups, which were mainly differentiated by psoralen and bergapten. The medicinal quality of Radix Fici Hirtae exhibited a southwest to southeast variation pattern across southern China, and its quality formation was influenced mostly by geographical environments. Our results provide references for the conservation, core collection construction and improvement of F. hirta.